Interval optimal reactive power reserve dispatch considering generator rescheduling. Issue 8 (1st May 2016) - Fang, Sidun; Cheng, Haozhong; Song, Yue; Ma, Zeliang; Zhu, Zhonglie; Zeng, Pingliang; Yao, Liangzhong
Abstract : Owing to the variations of loads and sustainable energy, the power injections and the load increment direction are of uncertainties, which pose great challenges to the traditional models of power system operation. To determine the effects of those uncertainties on the reactive power reserve (RPR), an interval optimal RPR dispatch with generator rescheduling (GR) is formulated. To evaluate the RPR interval more comprehensively, two sub‐models, namely the optimistic and pessimistic sub‐models, are built. The proposed method is applied to several IEEE systems to illustrate its effectiveness. Case tests show that, proper GR schemes can enhance the RPR of power system by postponing the limit hitting of the generator reactive power. The obtained RPR scheme shows better robustness to the uncertainties of power injections compared with that of the conventional RPR dispatches, and the restriction on the RPR interval widths also suggests the operating risk reduction.